The Effect of Total Physical Response Technique Toward the Students’ Speaking Ability at the First Grade Students’ of SMA Negeri 2 Kolaka - Lina Anisah (Universitas Negeri Makassar, 2019)
The research presents about the effect of total physical response technique toward the students’ speaking ability at the first grade of SMA Negeri 2 Kolaka. It was based on the research question” Is there any effect of total physical response technique toward the students’ speaking ability at the first grade students at SMA Negeri 2 Kolaka?’. The objective of this research was find out the data and information whether there is an effect of total physical response technique toward the students’ speaking ability at the first grade of SMA Negeri 2 Kolaka. The design of this research was pre-experimental design which one group pretest and posttest design. The subject of this research was class X3 of SMA Negeri 2 Kolaka consisted 22 students based on purposive sampling. The research consist of two variable, they are independent variable and dependent variable. The independent variable was Total Physical Response while the dependent variable was the students’ speaking ability. The instrument of the research was oral test which is recommended by Ur (1996). The data were analyzed by using inferential and descriptive statistic. The inferential statistic was used to examine the hypothesis, while the descriptive statistics was used to describe the students’ characteristics score such as mean score, frequency, minimun and maximun score in both pretest and posttest session. Based on findings in this research, it can be confirmed that the students’ mean score of post-test (3,9) is higher than pre-test (2,25). Standar deviation of post-test (0,541 ) was smaller than the the standard deviation of pre-test (0,668), and the value of tcount (11,2) was bigger than ttable (2,080) at the significant level 0,05 and degree of freedom = 21, it means that H0 was rejected and H1 was accepted. It can be concluded that there is an effect of total physical response technique toward the students’ speaking ability at the first grade of SMA Negeri 2 Kolaka.